Motivação de equipes em unidades de informação - Santos, Vanessa Lima dos [UNESP]; Almeida, Daniela Pereira dos Reis de [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (University Library System, University of Pittsburgh, 2011)
This article, through the revision of literature in the areas of Information Science and Administration, sought to rescue the theoretical yardstick about leadership, motivation, team works, competences, abilities and attitudes of leader. Beyond that was elaborated an exploratory study with directors/managers of university libraries. From the analysis of literature selected and the exploratory research, infers that the leader which works in units of information can develop some actions that are going to motivate the team, to which leads, as by example: implant participatory programs; establish challenging goals; encourage works in group; promote turnaround of post and functions; create results disclosure systems; stimulate the creativity; promote a good environment at work; promote education and training individual/group; defined clearly the responsibilities; delegate authority consciously, charge results; and others possibilities. In this manner, understands that leader that works in units of information is going to know the factors that enable the motivation of the team. For so much, it is necessary observe the aspirations of his collaborators and verify if organization has been capable of satisfy them. In that sense, falls to the informational professional qualify itself for perform that function.

Este artigo, por meio de uma revisão de literatura nas áreas de Ciência da Informação e Administração, buscou resgatar o referencial teórico sobre liderança, motivação, trabalho em equipe, competências, habilidades e atitudes do líder. Além disso, foi elaborado um estudo exploratório junto a diretores/gestores de bibliotecas universitárias. A partir da análise da literatura selecionada e da pesquisa exploratória, infere-se que o líder que atua em unidades de informação (UIs) pode desenvolver algumas ações que possibilitem motivar a equipe, a qual lidera, como por exemplo: implantar programas participativos; estabelecer metas desafiadoras; incentivar trabalhos em grupo; promover rotatividade de cargos e funções; criar sistemas de divulgação de resultados; estimular a criatividade; promover um bom ambiente de trabalho; promover educação e treinamento individual/grupo; definir claramente as responsabilidades; delegar autoridade conscientemente, cobrar resultados; entre tantas outras. Dessa maneira, entende-se que o líder que atua em unidades de informação necessita conhecer os fatores que possibilitam a motivação da equipe. Para tanto, é preciso observar as aspirações de seus colaboradores e verificar se a organização tem sido capaz de satisfazê-las. Assim, cabe ao profissional da informação capacitar-se para desempenhar bem essa função.
Teams motivation in units of information
Keywords: Motivação; Equipes Bibliotecárias; Capacitação de Equipes Bibliotecárias; Gestão de Unidades de Informação; Gestão de Pessoas